The Poetics of Travel and Space in Raja Rao’s ‘The Serpent and the Rope’ - Sinha, Dr. Arpana (Journal of Advanced Research in English & Education, 2025)
Raja Rao's The Serpent and the Rope (1960) is a landmark work of metaphysical fiction, wherein the traditional novelistic elements of travel and space are subverted and elevated to a profound philosophical poetics. This article argues that the protagonist Ramaswamy’s physical journeys across continents are not merely plot devices but a deliberate literary strategy to chart the contours of his inner, spiritual quest for non-duality ( Advaita ). The novel transforms geographical locations—from the timeless spiritual landscape of Benares to the fragmented intellectual space of Paris—into symbolic reflections of Ramaswamy’s evolving consciousness and his struggle to transcend the illusion of separateness. By deconstructing ten key facets of this poetics, this analysis demonstrates how Rao imbues every journey with a sense of pilgrimage, and every space with symbolic resonance, thereby making the very narrative a testament to the pursuit of Brahman. The article examines the dialectical relationship between external landscapes and internal states, the narrative’s non-linear structure as a representation of cyclical time, and the ultimate transformation of "home" from a physical location into a state of spiritual realization. Ultimately, the novel’s enduring legacy lies in its innovative poetic fusion of geography and metaphysics, rendering the journey from the illusory "serpent" to the immutable "rope" a profound spatial and narrative experience.